Answer:
See Explanation
Step-by-step explanation:
Given
[tex]Sum = 3\frac{1}{3}[/tex]
Required
Determine the fraction used
Since options, were not given. I'll answer on a general term
Assume, Austin used 2 fractions (a and b)
Such that:
[tex]a + b = 3\frac{1}{3}[/tex]
Also:
Assume that:
[tex]a = \frac{2}{3}[/tex]
Note that this could be any fraction, but I chose to use 2/
Make b the subject in [tex]a + b = 3\frac{1}{3}[/tex]
[tex]b = 3\frac{1}{3} - a[/tex]
[tex]b = 3\frac{1}{3} - \frac{2}{3}[/tex]
[tex]b = \frac{10}{3} - \frac{2}{3}[/tex]
Take LCM
[tex]b = \frac{10-2}{3}[/tex]
[tex]b = \frac{8}{3}[/tex]
[tex]b = 2\frac{2}{3}[/tex]
So, the fractions are:
[tex]a = \frac{2}{3}[/tex] and [tex]b = 2\frac{2}{3}[/tex]